Cardiorespiratory coordination reveals training-specific physiological adaptations - Garcia-Retortillo, S.; Gacto, M.; O`Leary, T. J.; Noon, M.; Hristovski, R.; Balagué, N.; Morris, M. G. (European Journal of Applied Physiology, 2019)
Purpose: To compare the effects of high-intensity interval training (HIIT) and moderate-intensity training (CONT), matched for total work, on cardiorespiratory coordination and aerobic fitness. Methods: This is a two-arm parallel group single-blind randomised study. Twenty adults were assigned to 6 weeks of HIIT or volume-matched CONT. Participants completed a progressive maximal cycling test before and after the training period. Principal component (PC) analysis was performed on the series of cardiorespiratory variables to evaluate dimensionality of cardiorespiratory coordination, before and after lactate turnpoint. PC1 eigenvalues were compared. Results: Both HIIT and CONT improved aerobic fitness (main effects of time, p < 0.001, Eta2p = 0.580), with no differences between groups. CONT decreased the number of PCs from two to one at intensities both below and above the lactate turnpoint; PC1 eigenvalues increased after CONT both below (Z = 2.08; p = 0.04; d = 0.94) and above the lactate turnpoint (Z = 2.10; p = 0.04; d = 1.37). HIIT decreased the number of PCs from two to one after the lactate turnpoint only; PC1 eigenvalues increased after HIIT above the lactate turnpoint (Z = 2.31; p = 0.02; d = 0.42). Conclusions: Although CONT and HIIT improved aerobic fitness to a similar extent, there were different patterns of change for cardiorespiratory coordination. These changes appear training-intensity specific and could be sensitive to investigate the individual response to endurance training.